2011
DOI: 10.1177/1403494811414242
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between gender segregation in the workplace and long-term sickness absence in Sweden

Abstract: The present study suggests that the gender composition in the workplace has an impact on the risk of LSA, especially among women. Our findings lend no support for Kanter's theory on the effects of being a token. Most likely, women's and men's different status positions have an impact on the different associations found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 24 publications
3
41
1
1
Order By: Relevance
“…In several European countries, women have higher rates of sickness absence than men [13-15]. Laaksonen et al [16] found that occupation accounted for half of the female sick leave episodes lasting more than 60 days and approximately one third of sick leave less than 60 days.…”
Section: Introductionmentioning
confidence: 99%
“…In several European countries, women have higher rates of sickness absence than men [13-15]. Laaksonen et al [16] found that occupation accounted for half of the female sick leave episodes lasting more than 60 days and approximately one third of sick leave less than 60 days.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of contact among workers within the same occupation at a workplace can vary, making both occupations and workplace gender composition valid units of analysis. The few studies that have focused on workplaces have analysed gender composition in relation to sickness absence and self-rated health [7-10], whereas mental health remains unexplored. Although mental illness accounts for a substantial part of the sickness absence in Sweden, especially for women [11], there is also a need for studies that focus on the mental ill- health aspects of the gender composition.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Kanter’s theory of “tokens”, researchers have suggested that being a small minority at the workplace could be extra harmful for health status [12,13]. However, this theory has not been supported empirically [7,14]. For women, the highest levels of sickness absence have been found at workplaces with a majority of women [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small handful of studies have examined whether gender imbalances in the workplace are associated with morbidity and differences in sickness absenteeism rates for males and females, but the evidence is mixed (Bryngelson, Hertzman, and Fritzell 2011;Mastekaasa 2005;Hensing and Alexanderson 2004;Svedberg et al 2009). Even less research has been conducted on the relationship between sex ratios and mortality risk.…”
Section: Introductionmentioning
confidence: 99%